A Minimum Break Load Analysis of Smith Bracket Using Finite Element Method (FEM) - Awwalin, Rodlitul; Sutiyo, Sutiyo (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
The study on the use of the Smith Bracket in towing operations highlights its critical role in securing towing connections, requiring strong structural integrity as mandated by IMO safety regulations. Using Finite Element Method (FEM) analysis, the stress distribution under various tensile loads was examined, and the simulation results indicate that the bracket design can safely withstand operational forces, making it suitable for towing applications.From the calculations: The Minimum Break Load (MBL) of the Smith Bracket is determined to be ±69 tons, Applying a Safety Factor (SF) of 4, The Safe Working Load (SWL) is calculated at 17.5 tons. These values indicate that the bracket meets safety requirements and is capable of withstanding operational loads without failure. The combination of IMO regulations, FEM simulations, and theoretical analysis ensures that the Smith Bracket is designed for safe and reliable towing operations.